2001
DOI: 10.1530/eje.0.1450743
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic patterns of adrenocortical carcinoma: morpho-functional correlates

Abstract: Objective: Adrenocortical scintigraphy has demonstrated clinical utility in the morpho-functional characterization of adrenal tumors. The aim of this study was to identify possible relationships between the scintigraphic pattern and endocrine and/or morphological data in a series of adrenocortical carcinomas. Design and Methods: Twenty-one patients with adrenocortical carcinoma (11 nonfunctioning and 10 hormone-secreting) were investigated with 75Se-methyl-nor-cholesterol scintigraphy. Clinical, hormonal, radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Uptake of radiocholesterol was present in 33.3% of patients; consequently, absence of uptake at adrenocortical scintigraphy was not a helpful marker of malignancy of the adrenal mass in our population. Similar findings have recently been described by Barzon et al [31], who reported increased tracer uptake in 30% of hypersecreting AC, regardless of the biochemical and histological features of the tumor.…”
Section: Discussionsupporting
confidence: 91%
“…Uptake of radiocholesterol was present in 33.3% of patients; consequently, absence of uptake at adrenocortical scintigraphy was not a helpful marker of malignancy of the adrenal mass in our population. Similar findings have recently been described by Barzon et al [31], who reported increased tracer uptake in 30% of hypersecreting AC, regardless of the biochemical and histological features of the tumor.…”
Section: Discussionsupporting
confidence: 91%
“…83,88,92 Typically, benign hypersecreting tumors, such as cortisol-, ALD-and androgen-secreting adenomas and non-hypersecreting adenomas, show radiocholesterol uptake, whereas primary and secondary adrenal malignancies appear as 'cold' masses, providing an overall sensitivity of 71-100% and specificity of 50-100%. 83,88,92,93,[95][96][97][98][99][100][101] A large study of 229 patients with abnormal adrenal anatomy depicted by CT who were evaluated by injecting 131 I-NP-59 concluded that in the absence of hormonal dysfunction, the presence of concordant CT and 131 I-NP-59 scans is characteristic of functioning, but not hypersecretory, benign adrenocortical adenomas. Discordant CT and 131 I-NP-59 scans are suggestive of nonfunctioning, space-occupying, adrenal lesions.…”
Section: Functional Imaging Modalitiesmentioning
confidence: 99%
“…Radiocholesterol scintigraphy can have an important role in diagnosing adrenocortical carcinomas, but in the present case the poor differentiation of the mass did not lead to tracer uptake. Moreover, this technique is used to identify nonviewable lesions but this was not the case and the risk of hemorrhage of the adrenal lesion prompted surgical resection 8,9 .…”
Section: Discussionmentioning
confidence: 99%